Advanced spectroscopic analyses on a:C-H materials: Revisiting the EELS characterization and its coupling with multi-wavelength Raman spectroscopy. (February 2017) - Lajaunie, L.; Pardanaud, C.; Martin, C.; Puech, P.; Hu, C.; Biggs, M.J.; Arenal, R.
Abstract: Hydrogenated amorphous carbon thin films (a:C-H) are very promising materials for numerous applications. The growing of relevance of a:C-H is mainly due to the long-term stability of their outstanding properties. For improving their performances, a full understanding of their local chemistry is highly required. Fifteen years ago, electron energy-loss spectroscopy (EELS), developed in a transmission electron microscope (TEM), was the technique of choice to extract such kind of quantitative information on these materials. Other optical techniques, as Raman spectroscopy, are now clearly favored by the scientific community. However, they still lack of the spatial resolution offered by TEM-EELS. In addition, nowadays, the complexity of the physics phenomena behind EELS is better known. Here, a:C-H thin films have been isothermally annealed and the evolution of their physical and chemical parameters have been monitored at the local and macroscopic scales. In particular, chemical in-depth inhomogeneities and their origins are highlighted. Furthermore, a novel procedure to extract properly and reliably quantitative chemical information from EEL spectra is presented. Finally, the pertinence of empirical models used by the Raman community is discussed. These works demonstrate the pertinence of the combination of local and macroscopic analyses for a proper study of such complex materials. Graphical abstract: